EFEKTIVITAS PEMBERIAN INFUSED WATER MENTIMUN TERHADAP PENURUNAN TEKANAN DARAH PADA PENDERITA HIPERTENSI - Arum Putri Mohamad; Brajakson Siokal; Rizqy Iftitah Alam; Andi Mappanganro (CV. Adiba Aisha Amira, 2025)
Hypertension is one of the public health problems with increasing prevalence every year and has the potential to cause complications such as stroke, heart failure, and kidney damage. Non-pharmacological efforts are an alternative intervention that is increasingly used, one of which is cucumber water infused therapy which is believed to have a diuretic effect and antioxidant content to help lower blood pressure. The purpose of this study is to determine the effectiveness of cucumber infused water in reducing blood pressure in hypertensive patients in the working area of the Maccini Sawah Health Center. This study uses a pre-experimental design with a one group pretest–posttest approach. Blood pressure data were measured before and after administration of cucumber infused water during the intervention period. The instruments used were observation sheets and interviews. The results showed that there was a decrease in systolic and diastolic blood pressure after cucumber infused water intervention. The decrease shows the body's positive response to cucumber's main content such as potassium, water, and flavonoids which play a role in reducing vascular resistance and improving hydration. Therefore, cucumber infused water is effective in lowering blood pressure in people with hypertension and can be recommended as a supportive non-pharmacological therapy in primary health care facilities